PELATIHAN PENGGUNAAN MEDIA PEMBELAJARAN MANIPULATIF UNTUK MENANAMKAN KONSEP BANGUN RUANG BAGI GURU DI SDN 67 KOTA BENGKULU - Neza Agusdianita; Viktoria Karjiyati (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2021)
The school that is being used as a partner for the Community Service activity that is being proposed is SDN 67 Surabaya District, Bengkulu City. The objectives in this PPM are as follows (1) to increase teacher knowledge about Realistic Mathematical Education (RME) learning approaches that can help students understand mathematics learning materials more easily, (2) to increase teacher knowledge about various mathematics learning media that are in accordance with characteristics of elementary school students, especially for the concept of building space and (3) to improve the skills of teachers in using manipulative learning media, especially for the concept of building space. The method used in this activity is training and mentoring. The training was carried out to increase the knowledge and insight of teachers in using manipulative learning media for the concept of building space in elementary schools. After the target teachers have mastered the knowledge and skills, they are then asked to apply the skills they already have in the actual learning process in the classroom. The result of this community service activity is the preparation of training tools for the application of manipulative learning media for the concept of building space for teachers at SDN 67 Bengkulu City. The Training Activity for Making Manipulative Learning Media for the Concept of Teacher's Space Building at SDN 67 Bengkulu City was held on Saturday, August 23, 2018 until August 28, 2018. 67 Bengkulu City has been implemented well. The purpose of this activity has been achieved.